Delayed-Onset Surgical Site Infection after Sphenoid Wing Meningioma Resection: A Case Report Highlighting Diagnostic and Management Challenges - Sumargo, Sheila; Guata Naibaho; Roland Sidabutar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Surgical site infections (SSIs) following craniotomy, while uncommon, pose significant risks. Delayed-onset infections can present diagnostic and management challenges. We report a case of delayed-onset SSI after sphenoid wing meningioma resection, emphasizing the importance of vigilance and prompt intervention. Case presentation: A 26-year-old male underwent craniotomy for a right sphenoid wing meningioma. He presented 13 days post-operatively with a fluctuant swelling at the surgical site. Imaging revealed a subgaleal and epidural abscess. He underwent craniectomy, debridement, and antibiotic therapy, resulting in complete resolution. Conclusion: Delayed-onset SSIs after craniotomy necessitate a high index of suspicion. Early diagnosis and aggressive management, including surgical debridement and appropriate antibiotics, are crucial for optimal outcomes.